Blue ocean strategy how to create uncontested market space and make the competition irrelevant - Kim, W. Chan; Mauborgne, Renée (Harvard Business School Press, 2005)
In a book that challenges everything you thought you knew about the requirements for strategic success, Kim and Mauborgne argue that cutthroat competition results in nothing but a bloody red ocean of rivals fighting over a shrinking profit pool. Based on a study of 150 strategic moves spanning more than a hundred years and 30 industries, the authors argue that lasting success comes not from battling competitors, but from creating "blue oceans"--Untapped new market spaces ripe for growth. Such strategic moves--which the authors call "value innovation"--create powerful leaps in value that often render rivals obsolete for more than a decade. Blue Ocean Strategy presents a systematic approach to making the competition irrelevant.--From publisher description.
Literaturverzeichnis Seite 223-229
Keywords: Compétitivité; Concurrence; Marktsegmentatie; Produit nouveau; Produits nouveaux; Segmentation du marché; Strategisch management; Market segmentation; New products; Unternehmen; Marktsegmentierung; Kooperation; Markterschließung; Neues Produkt; Marktergebnis; Guide (Descripteur de forme)